2020
DOI: 10.34172/apb.2021.033
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and In vitro Studies Reveal the Importance of p53, PPARG and Notch Signaling Pathway in Inhibition of Breast Cancer Stem Cells by Hesperetin

Abstract: Purpose: The failure of chemotherapy in breast cancer is caused by breast cancer stem cells (BCSCs), a minor population of cells in bulk mammary tumors. Previously, hesperetin, a citrus flavonoid, showed cytotoxicity in several cancer cells and increased cytotoxicity of doxorubicin and cisplatin. Hesperetin also inhibited osteogenic and adipocyte differentiation, however, a study of the effect of hesperetin on BCSCs has not yet been performed. Methods: In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…MDM2 encodes the MDM2 protein, which acts as a major negative regulator of the tumor suppressor p53 [ 36 ]. p53 is a barrier to cancer cell growth [ 37 ], and it is a druggable target, along with ERα [ 38 ]. These PTGs are potential targets for OA in overcoming tamoxifen resistance in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…MDM2 encodes the MDM2 protein, which acts as a major negative regulator of the tumor suppressor p53 [ 36 ]. p53 is a barrier to cancer cell growth [ 37 ], and it is a druggable target, along with ERα [ 38 ]. These PTGs are potential targets for OA in overcoming tamoxifen resistance in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies confirmed that PPARG activation facilitates the anti-tumor effect of 6-iodolactone (Nava-Villalba et al, 2015) and hesperetin (Hermawan et al, 2021). According to a study carried by Liu stated that datasets of GEO revealed that the high expression of PPARG was associated with better prognosis in BRCA (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…HSP can suppress cancer cell proliferation, viability, migration, invasion, mammosphere, and colony formation and stimulate DNA damage and apoptosis. Being a promising anticancer agent, HSP (100 μM) showed cytotoxicity on cells and prevented mammosphere, colony formation, and migration through elevating the mRNA level of p53, NOTCH1, PPARG, and reduced β-catenin resulted in apoptosis with cell cycle arrest G0/G1 phase in MCF-7 breast cancer cells [56]. Another study on a similar cell line by Choi showed that HSP (1-100 μM) administration induces apoptosis and inhibits cell proliferation after 48-72 h treatment [57].…”
Section: Breast Cancermentioning
confidence: 99%